PENDAMPINGAN PETANI DALAM PERENCANAAN DESAIN PRASARANA PADI SAWAH LAHAN RAWA DI DESA TOPANG KEPULAUAN MERANTI - Dewi , Novia; Herlon, Meki; Sutikno, Sigit; Metananda, Arya Arismaya; Gunawan, Wawan; Mubarak, Mubarak; Qomar, Nurul (JP2N : Jurnal Pengembangan Dan Pengabdian Nusantara, 2025)
The target location for land optimization in the Kepulauan Meranti Regency is situated in Topang Village, Rangsang District. Several constraints were encountered in the development planning of infrastructure for swamp paddy fields, including the remote location, high costs of transportation and materials, among others. This community service project, therefore, aims to provide assistance in the planning process for cost estimation and priority scaling of the infrastructure to be developed for the paddy fields in Topang Village. The objective of this assistance is to align the available funding with the feasible infrastructure projects. The target participants for this activity are paddy farmers in Topang Village with a cropping index of 100 per year, who are members of a farmers' group. The service method involved facilitation, opinion surveys, and discussions concerning the infrastructure priorities for the Topang Village paddy fields. The results indicate that the participants gained an understanding of the priorities for utilizing the grant funds from the Ministry of Agriculture and the types of infrastructure to be prioritized, such as channel normalization, the construction of automatic water gates, canal barriers, farm access bridges, and the procurement of water pumps.